The Principle of Proportionality of Crime and Punishment in International Documents - Dachak, Hadi (International journal of multicultural and multireligious understanding, 2021)
Observance of the principle of proportionality is one of the basic requirements of fairness and justice in all matters, including the determination of punishment and its purpose is to match the amount of punishment with the amount of guilt of the perpetrator. This principle is a logical basis for punishment and the factor of its legitimacy. Of course, it should be noted that the proportionality of crime and punishment is a fluid and relative matter, the regulation of which according to the principles of most criminal schools is a function of the ideology and values that govern societies. According to the principle of proportionality, justice and fairness require that the offender be entitled only to the punishment of the crime committed which is based on the severity of the crime and the situation of the victim, the situation of the offender, the circumstances of the crime, etc., the case and the action take place. In other words, there must be coordination and balance between crime and punishment in order to ensure justice. Although given the relative meaning of the principle of proportionality, it does not seem to be possible for punishment to be equal to a crime, in other words, it is true. Proportion between crime and punishment does not mean a precise mathematical proportion, but a proper ratio between crime and punishment can be established, although it does not lead to complete equality. International criminal law oversees the duty to protect international public order and to guarantee international justice. For its realization, the observance of the principle of proportionality is undoubtedly evident. As in the International Criminal Court, the determination of punishment is based on the achievements of criminology in relation to the motives of crimes and the classification of offenders and the personality of the offender, which is reflected in Article 145 of the Rules of Procedure and the evidence of the Court